Enhanced polyglycolic acid as well as preparation method and application thereof
By using tin-doped nanocatalysts in the polymerization process of polyglycolic acid, the problems of insufficient mechanical properties and thermal degradation and yellowing in the prior art are solved, and high mechanical properties and stability are achieved.
Patent Information
- Application Number
- CN202311333686.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
AI Technical Summary
When the prior art enhances the mechanical properties of polyglycolic acid, it is easy to cause thermal degradation and yellowing of polyglycolic acid, affecting product quality.
The nanocatalyst doped tin is used as the catalyst for glycolide polymerization, and the mechanical properties of polyglycolic acid are improved by retaining the nanocatalyst during the polymerization process.
Through this method, the tensile strength of polyglycolic acid reaches more than 110MPa and the bending strength reaches more than 180MPa, which significantly improves its mechanical properties, and avoids the problems of thermal degradation and yellowing.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyglycolic acid preparation, and in particular to a reinforced polyglycolic acid and a preparation method and application thereof. Background Art
[0002] At present, biodegradable polymer materials are increasingly widely used due to their good biodegradability. Among them, the biodegradable polymer polyglycolic acid (PGA) has excellent gas barrier properties, good mechanical processing properties, and outstanding biodegradability. It is widely used in medical materials (surgical sutures and drug sustained-release capsules), packaging materials (bottle linings), membrane materials (ground membranes) and engineering plastics (petroleum field), etc.
[0003] Some application scenarios have high requirements for the mechanical properties of PGA, and it needs to be enhanced and modified. The existing technology usually enhances and modifies by adding inorganic additives. Taking patent CN115322538A as an example, the existing technology usually extrudes PGA with a large amount of inorganic additives, but this processing process easily causes thermal degradation and yellowing of PGA, affecting product quality.
[0004] Therefore, there is an urgent need for a reinforcement modification method that does not require the above-mentioned blending and extrusion processing method, so that the obtained polyglycolic acid has good mechanical strength. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a reinforced polyglycolic acid and its preparation method and application. The present invention uses a tin-doped nanocatalyst as a catalyst for the polymerization of glycolide. After polymerization, the nanocatalyst can play an in-situ reinforcement role and improve the mechanical properties of PGA.
[0006] One of the objects of the present invention is to provide a reinforced polyglycolic acid, comprising polyglycolic acid and a tin-doped nanocatalyst.
[0007] In a preferred embodiment of the present invention,
[0008] The tin content of the tin-doped nanocatalyst is 10 to 60 wt%, preferably 20 to 50 wt%; and / or,
[0009] The particle size of the tin-doped nanocatalyst is in the range of 20 to 900 nm, preferably 20 to 700 nm; and / or, the average particle size is 20 to 900 nm, preferably 100 to 500 nm. The particle size of the tin-doped nanocatalyst is consistent with its particle size in polyglycolic acid, and the particle size range is 20 to 900 nm, preferably 20 to 700 nm; and / or, the average particle size is 20 to 900 nm, preferably 100 to 500 nm.
[0010] In a preferred embodiment of the present invention,
[0011] The tin-doped nanocatalyst is obtained by reacting and co-precipitating components including a tin-containing compound and a titanate compound; preferably, the method for preparing the tin-doped nanocatalyst includes the steps of reacting and precipitating the components including the tin-containing compound and tetrabutyl titanate in a solvent, separating and drying to obtain the tin-doped nanocatalyst; further preferably, the method for preparing the tin-doped nanocatalyst includes the steps of mixing the components including the tin-containing compound and the titanate compound in a solvent A to obtain a suspension, adding the suspension to a solvent B containing an acidic substance, and separating and drying after sufficient reaction and precipitation to obtain the tin-doped nanocatalyst.
[0012] In a preferred embodiment of the present invention,
[0013] The tin-containing compound is selected from conventional tin-containing compounds in the field of polyglycolic acid preparation in the prior art, preferably selected from at least one of stannous octoate, tetraphenyltin, tetrabutyl stannate, stannous chloride, stannous chloride dihydrate, tin chloride, stannous acetylacetonate, tin lactate, and tin ethoxide; and / or,
[0014] The titanate compound is selected from at least one of n-butyl titanate, tert-butyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetraoctadecyl orthophthalate, preferably selected from at least one of n-butyl titanate, tert-butyl titanate, tetraethyl titanate, and tetraisopropyl titanate; and / or,
[0015] The mass ratio of the tin-containing compound to the titanate compound is (0.1-10):1, preferably (0.4-5):1, and more preferably (0.4-1.5):1.
[0016] In a preferred embodiment of the present invention,
[0017] The solvent A is selected from at least one of methanol, ethanol, isopropanol and n-butanol; and / or,
[0018] The mass ratio of the solvent A to the tin-containing compound is (10-1000):1, preferably (50-500):1; and / or,
[0019] The acidic substance is selected from at least one of hydrochloric acid, acetic acid, oxalic acid, phosphoric acid and sulfuric acid; and / or,
[0020] The mass ratio of the acidic substance to the tin-containing compound is (0.0001-50):1, preferably (0.01-20):1; and / or,
[0021] The solvent B is selected from at least one of water, methanol, ethanol, isopropanol and n-butanol; and / or,
[0022] The mass ratio of the solvent B to the acidic substance is (5-10000):1, preferably (10-500):1.
[0023] In a preferred embodiment of the present invention,
[0024] The reaction precipitation conditions include: a temperature of 0 to 110° C., preferably 30 to 80° C.; and / or a time of 0.1 to 20 h, preferably 0.5 to 10 h; and / or,
[0025] The drying conditions include: vacuum drying at 40-100° C. for 2-24 hours.
[0026] In a preferred embodiment of the present invention,
[0027] After separation and drying, the method further includes a crushing step, and the crushing can adopt any crushing method in the prior art; preferably, after crushing, the method further includes a step of vacuum dehydration at 60-150° C. for 1-10 hours.
[0028] In a preferred embodiment of the present invention,
[0029] The content of the tin-doped nanocatalyst in the reinforced polyglycolic acid is 10 to 1000 ppm (in the present invention, ppm is equivalent to mg / kg), preferably 100 to 500 ppm.
[0030] In a preferred embodiment of the present invention,
[0031] The reinforced polyglycolic acid has a tensile strength of more than 110 MPa, preferably 110-150 MPa; and / or a flexural strength of more than 180 MPa, preferably 180-220 MPa.
[0032] In a preferred embodiment of the present invention,
[0033] The enhanced polyglycolic acid is prepared by a preparation step comprising polymerizing glycolide in the presence of a tin-doped nanocatalyst and retaining the tin-doped nanocatalyst in the reaction product.
[0034] Conventional components in the art, such as degradable polymers, may also be added to the enhanced polyglycolic acid. The degradable polymer is at least one of PBAT, PBS, PBST, starch, etc., and the amount used is also a conventional amount. Those skilled in the art may add it according to actual conditions.
[0035] The second object of the present invention is to provide a method for preparing enhanced polyglycolic acid according to one of the objects of the present invention, comprising the steps of polymerizing glycolide in the presence of a tin-doped nanocatalyst and retaining the tin-doped nanocatalyst in the reaction product to obtain enhanced polyglycolic acid.
[0036] In a preferred embodiment of the present invention,
[0037] The acid value of the glycolide is 0.1 to 50 mol / t, preferably 0.2 to 25 mol / t; and / or, the water content of the glycolide is 10 to 1000 ppm, preferably 20 to 500 ppm; and / or,
[0038] The content of the tin-doped nano catalyst in glycolide is 10 to 1000 ppm, preferably 100 to 500 ppm.
[0039] In a preferred embodiment of the present invention,
[0040] The polymerization temperature is 180-240° C., preferably 200-220° C.; and / or the polymerization time is 0.1-10 h, preferably 0.2-5 h.
[0041] The third object of the present invention is to provide an application of the enhanced polyglycolic acid of the first object of the present invention or the enhanced polyglycolic acid obtained by the preparation method of the second object of the present invention in the fields of medical materials, packaging materials, film materials, and engineering plastics.
[0042] Beneficial effects of the present invention:
[0043] In order to optimize the preparation method of enhanced polyglycolic acid, the present invention provides a preparation method of enhanced polyglycolic acid, comprising: polymerizing glycolide in the presence of a tin-doped nanocatalyst to obtain enhanced polyglycolic acid. The tin-doped nanocatalyst remains in the polyglycolic acid system after the polymerization reaction is completed, and the nanoparticles and the polyglycolic acid have a physicochemical effect, thereby improving the mechanical properties of the polyglycolic acid. Although the catalyst (tin-containing compound) used in the prior art also remains in the polyglycolic acid system after the polymerization reaction is completed, since the tin-containing compound structure is a single molecule, it is impossible to achieve the in-situ enhancement effect of the nanoparticle catalyst of the present application. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0045] The raw materials used in the examples are all conventional commercially available raw materials.
[0046] [Injection molding and mechanical properties test]: Use an injection molding machine to prepare 1BA dumbbell-shaped specimens and specimens with a length of 80.0 mm, a width of 10.0 mm, and a thickness of 4.0 mm. Use an Intron 3344 universal tensile machine to perform tensile tests and three-point bending tests on them at a test rate of 5 mm / min. The test standards refer to the national standards GB / T 1040.2-2022 and GB / T 9341-2008.
[0047] The tin content in the tin-doped nanocatalyst is obtained by instrumental characterization, and the testing instrument is an X-ray energy spectrometer, model Oxford X-MaxN 150EDS.
[0048] The particle size of the tin-doped nanocatalyst was measured using a Nova NanoSEM 450 scanning electron microscope.
[0049] [Preparation of tin-doped nanocatalyst 1]
[0050] Mix 2.5g of tetrabutyl titanate, 1.0g of stannous chloride and 200mL of anhydrous ethanol and stir for 1h to obtain a uniform suspension. At the same time, dissolve 10mL of oxalic acid (oxalic acid content greater than 99%) in 200ml of ethanol / water (volume ratio of ethanol to water = 1) solution and stir at 50°C for 1h. Then slowly drip the suspension into the solution at 50°C. After all the dripping, keep stirring at 50°C for 6h, and let it stand for 10h to precipitate particles. After filtering the precipitate, vacuum dehydrate at 60°C for 12h, crush it, and vacuum dehydrate at 120°C for 2h to obtain tin-doped nanocatalyst 1 with a tin content of 28%, a particle size range of 40 to 500nm, and an average particle size of 250nm.
[0051]
Preparation of tin-doped nanocatalyst 2
[0052] Mix 1.0g of tetraethyl titanate, 1.0g of stannous octoate and 100mL of anhydrous ethanol and stir for 1h to obtain a uniform suspension. At the same time, dissolve 12mL of oxalic acid (oxalic acid content greater than 99%) in 150ml of ethanol / water (volume ratio of ethanol to water = 1) solution and stir at 50°C for 1h. Then slowly drip the suspension into the solution at 50°C. After all the dripping, keep stirring at 50°C for 6h, and let it stand for 10h to precipitate particles. After filtering the precipitate, vacuum dehydrate at 60°C for 12h, crush it, and vacuum dehydrate at 120°C for 2h to obtain tin-doped nanocatalyst 2, with a tin content of 43%, a particle size range of 120-700nm, and an average particle size of 500nm.
[0053]
Preparation of tin-doped nanocatalyst 3
[0054] Mix 2.0g of tert-butyl titanate, 1.0g of stannous acetylacetonate and 250mL of anhydrous ethanol and stir for 1h to obtain a uniform suspension. At the same time, dissolve 10mL of oxalic acid (oxalic acid content greater than 99%) in 200ml of ethanol / water (volume ratio of ethanol to water = 1) solution and stir at 50°C for 1h. Then slowly drip the suspension into the solution at 50°C. After all the dripping, keep stirring at 50°C for 6h, and let it stand for 10h to precipitate particles. After filtering the precipitate, vacuum dehydrate at 60°C for 12h, crush it, and vacuum dehydrate at 120°C for 2h to obtain tin-doped nanocatalyst 3 with a tin content of 22%, a particle size range of 20 to 300nm, and an average particle size of 100nm.
[0055] [Example 1]
[0056] 300 ppm of the above-mentioned tin-doped nanocatalyst 1 was added to glycolide with an acid value of 5 mol / t and a water content of 100 ppm, and polymerization was carried out in a polymerization reactor at a polymerization temperature of 210°C and a polymerization time of 30 minutes to obtain enhanced polyglycolic acid. The resin slices were characterized using a transmission electron microscope (Tecnai 20S-TWIN), and it was observed that the particle size of the nanocatalyst in the enhanced polyglycolic acid ranged from 40 to 500 nm, and the average particle size was 250 nm. The obtained enhanced polyglycolic acid had a tensile strength of 115 MPa and a flexural strength of 190 MPa.
[0057] [Example 2]
[0058] 200 ppm of the above-mentioned tin-doped nanocatalyst 2 was added to glycolide with an acid value of 8 mol / t and a water content of 180 ppm, and polymerization was carried out in a polymerization reactor at a polymerization temperature of 220°C and a polymerization time of 15 minutes to obtain enhanced polyglycolic acid. The resin slices were characterized using a transmission electron microscope (Tecnai 20S-TWIN), and it was observed that the particle size of the nanocatalyst in the enhanced polyglycolic acid ranged from 120 to 700 nm, with an average particle size of 500 nm. The obtained enhanced polyglycolic acid had a tensile strength of 128 MPa and a flexural strength of 205 MPa.
[0059] [Example 3]
[0060] 600 ppm of the above-mentioned tin-doped nanocatalyst 3 was added to glycolide with an acid value of 5 mol / t and a water content of 100 ppm, and polymerization was carried out in a polymerization reactor at a polymerization temperature of 218°C and a polymerization time of 12 minutes to obtain enhanced polyglycolic acid. The resin slices were characterized using a transmission electron microscope (Tecnai 20S-TWIN), and it was observed that the particle size of the nanocatalyst in the enhanced polyglycolic acid ranged from 20 to 300 nm, with an average particle size of 100 nm. The obtained enhanced polyglycolic acid had a tensile strength of 135 MPa and a flexural strength of 210 MPa.
[0061] [Example 4]
[0062] 800 ppm of the above-mentioned tin-doped nanocatalyst 3 was added to glycolide with an acid value of 8 mol / t and a water content of 180 ppm, and polymerization was carried out in a polymerization reactor at a polymerization temperature of 218°C and a polymerization time of 10 minutes to obtain enhanced polyglycolic acid. The resin slices were characterized using a transmission electron microscope (Tecnai 20S-TWIN), and it was observed that the particle size of the nanocatalyst in the enhanced polyglycolic acid ranged from 20 to 300 nm, with an average particle size of 100 nm. The obtained enhanced polyglycolic acid had a tensile strength of 145 MPa and a flexural strength of 215 MPa.
[0063] [Comparative Example 1]
[0064] Stannous chloride was added to glycolide with an acid value of 5 mol / t and a water content of 100 ppm, and the tin content was controlled to be consistent with that in Example 1. Polymerization was carried out in a polymerization reactor at a polymerization temperature of 210°C and a polymerization time of 30 minutes to obtain polyglycolic acid. The resin slice was characterized by a transmission electron microscope (Tecnai 20S-TWIN), and no nanoparticles were observed. The obtained polyglycolic acid had a tensile strength of 98 MPa and a flexural strength of 164 MPa.
[0065] [Comparative Example 2]
[0066] Stannous chloride was added to glycolide with an acid value of 5 mol / t and a water content of 100 ppm, and the tin content was controlled to be consistent with that in Example 1. Polymerization was carried out in a polymerization reactor at a polymerization temperature of 210°C and a polymerization time of 30 minutes. After obtaining polyglycolic acid, it was melt-blended with 300 ppm of tin-doped nanocatalyst 1 (blended for 10 minutes at 220°C in an internal mixer). The resin slices were characterized by transmission electron microscopy, and it was observed that the catalyst size ranged from 40 to 500 nm, with an average size of 250 nm. The tensile strength of the melt blend was measured to be 78 MPa, and the flexural strength was 124 MPa.
[0067] [Comparative Example 3]
[0068] Stannous chloride was added to glycolide with an acid value of 5 mol / t and a water content of 100 ppm, and the tin content was controlled to be consistent with that in Example 1. Polymerization was carried out in a polymerization reactor at a polymerization temperature of 210°C and a polymerization time of 30 minutes. After obtaining polyglycolic acid, it was melt-blended with tetrabutyl titanate (the titanium content was controlled to be consistent with that in Example 1) (blended for 10 minutes at 220°C in an internal mixer). The resin slices were characterized by transmission electron microscopy, and no nanoparticles were observed. The tensile strength of the melt blend was measured to be 82 MPa, and the bending strength was 131 MPa.
[0069] [Comparative Example 4]
[0070] Stannous chloride and tetrabutyl titanate were added to glycolide with an acid value of 5 mol / t and a water content of 100 ppm, and the tin content and titanium content were controlled to be consistent with those in Example 1. Polymerization was carried out in a polymerization reactor at a polymerization temperature of 210°C and a polymerization time of 30 minutes to obtain polyglycolic acid. The resin slices were characterized by a transmission electron microscope (Tecnai 20S-TWIN), and no nanoparticles were observed. The obtained polyglycolic acid had a tensile strength of 95 MPa and a flexural strength of 167 MPa.
[0071] It can be seen from Examples 1-4 that the tensile strength of the reinforced polyglycolic acid obtained in the present invention is above 110 MPa, and the flexural strength is above 180 MPa. It can be seen that the present invention uses a tin-doped nanocatalyst as a catalyst for the polymerization of glycolide, and the nanocatalyst can play an in-situ reinforcement role after polymerization, thereby improving the mechanical properties of PGA.
[0072] It can be seen from Example 1 and Comparative Examples 2-3 that the "in situ enhancement" effect produced by the participation of the nanocatalyst prepared from components including tin compounds and titanate compounds in the polymerization reaction of the present invention is superior to the enhancement effect of adding nanoparticles or supplementing tetrabutyl titanate in post-processing.
[0073] It can be seen from Example 1 and Comparative Example 4 that the in-situ enhancement effect can only be achieved when the tin compound and the titanate compound are prepared into nanocatalysts using the specific preparation method of the present invention. Simply adding these two substances during the polymerization process cannot achieve the in-situ enhancement effect of the present invention.
[0074] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0075] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0076] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0077] The endpoints and any values of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0078] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0079] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A reinforced polyglycolic acid, comprising polyglycolic acid and a tin-doped nanocatalyst.
2. The reinforced polyglycolic acid according to claim 1, characterized in that: The tin content of the tin-doped nanocatalyst is 10 to 60 wt%, preferably 20 to 50 wt%; and / or, The particle size of the tin-doped nanocatalyst is in the range of 20 to 900 nm, preferably 20 to 700 nm.
3. The reinforced polyglycolic acid according to claim 1, characterized in that: The tin-doped nanocatalyst is obtained by co-precipitation of components including a tin-containing compound and a titanate compound; preferably, the preparation method of the tin-doped nanocatalyst includes the steps of mixing the components including the tin-containing compound and the titanate compound in a solvent A to obtain a suspension, adding the suspension to a solvent B containing an acidic substance, and separating and drying after sufficient reaction and precipitation to obtain the tin-doped nanocatalyst.
4. The reinforced polyglycolic acid according to claim 3, characterized in that: The tin-containing compound is at least one selected from stannous octoate, tetraphenyltin, tetrabutyl stannate, stannous chloride, stannous chloride dihydrate, tin chloride, stannous acetylacetonate, tin lactate, and tin ethoxide; and / or, The titanate compound is selected from at least one of n-butyl titanate, tert-butyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetraoctadecyl orthophthalate; and / or, The mass ratio of the tin-containing compound to the titanate compound is (0.1-10):1, preferably (0.4-5):
1.
5. The reinforced polyglycolic acid according to claim 3, characterized in that: The solvent A is selected from at least one of methanol, ethanol, isopropanol and n-butanol; and / or, The mass ratio of the solvent A to the tin-containing compound is (10-1000):1, preferably (50-500):1; and / or, The acidic substance is selected from at least one of hydrochloric acid, acetic acid, oxalic acid, phosphoric acid and sulfuric acid; and / or, The mass ratio of the acidic substance to the tin-containing compound is (0.0001-50):1, preferably (0.01-20):1; and / or, The solvent B is selected from at least one of water, methanol, ethanol, isopropanol and n-butanol; and / or, The mass ratio of the solvent B to the acidic substance is (5-10000):1, preferably (10-500):
1.
6. The reinforced polyglycolic acid according to claim 3, characterized in that: The reaction precipitation conditions include: a temperature of 0 to 110° C., preferably 30 to 80° C.; and / or a time of 0.1 to 20 h, preferably 0.5 to 10 h; and / or, The drying conditions include: vacuum drying at 40-100° C. for 2-24 hours.
7. The reinforced polyglycolic acid according to any one of claims 1 to 6, characterized in that: The content of the tin-doped nano catalyst in the reinforced polyglycolic acid is 10 to 1000 ppm, preferably 100 to 500 ppm.
8. The reinforced polyglycolic acid according to any one of claims 1 to 6, characterized in that: The reinforced polyglycolic acid has a tensile strength of more than 110 MPa, preferably 110-150 MPa; and / or a flexural strength of more than 180 MPa, preferably 180-220 MPa.
9. The reinforced polyglycolic acid according to any one of claims 1 to 6, characterized in that: The enhanced polyglycolic acid is prepared by a preparation step comprising polymerizing glycolide in the presence of a tin-doped nanocatalyst and retaining the tin-doped nanocatalyst in the reaction product.
10. A method for preparing the enhanced polyglycolic acid according to any one of claims 1 to 9, comprising the steps of polymerizing glycolide in the presence of a tin-doped nanocatalyst and retaining the tin-doped nanocatalyst in the reaction product to obtain the enhanced polyglycolic acid.
11. The method according to claim 10, characterized in that: The acid value of the glycolide is 0.1 to 50 mol / t, preferably 0.2 to 25 mol / t; and / or, the water content of the glycolide is 10 to 1000 ppm, preferably 20 to 500 ppm; and / or, The content of the tin-doped nano catalyst in glycolide is 10 to 1000 ppm, preferably 100 to 500 ppm.
12. The method according to claim 10, characterized in that: The polymerization temperature is 180-240° C., preferably 200-220° C.; and / or the polymerization time is 0.1-10 h, preferably 0.2-5 h.
13. Use of the reinforced polyglycolic acid according to any one of claims 1 to 9 or the reinforced polyglycolic acid obtained by the preparation method according to any one of claims 10 to 12 in the fields of medical materials, packaging materials, film materials and engineering plastics.